2007
DOI: 10.1080/14634980701708057
|View full text |Cite
|
Sign up to set email alerts
|

Towards sustainable exploitation of Nile perch consequential to regulated fisheries in Lake Victoria

Abstract: Understanding fluctuations in the abundance and distribution of fishery resources over space and time is fundamental in order to address concerns about their sustainability and the basis for their management. Stock assessment studies were conducted on Lake Victoria from 1997 to 2001, with the aim to assess the status of the stocks, in particular of Nile perch. This paper summarises the findings for the Tanzanian part of the lake and makes reference to the Kenyan and Ugandan national waters for comparison. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…By 2007 the total catch had risen to around 1,000,000 t with the Nile perch catch being around 240,000 t (25% of the total) with Rastrineobola, Oreochromis and haplochromines making up the balance. The decreased proportion of Nile perch in the catch led to concerns that the stock was becoming overfished (MATSUISHE et al, 2006;NJIRU et al, 2007;MKUMBO et al, 2007) and the biomass of Nile perch in the lake has indeed declined significantly over the last decade (LVFO, 2008). SIMONIT and PERRINGS (2005) asserted that landings of all [our italics] fish had declined since 1994 and, while recognising the contribution of overfishing, suggested that eutrophication was an important factor.…”
Section: Introductionmentioning
confidence: 97%
“…By 2007 the total catch had risen to around 1,000,000 t with the Nile perch catch being around 240,000 t (25% of the total) with Rastrineobola, Oreochromis and haplochromines making up the balance. The decreased proportion of Nile perch in the catch led to concerns that the stock was becoming overfished (MATSUISHE et al, 2006;NJIRU et al, 2007;MKUMBO et al, 2007) and the biomass of Nile perch in the lake has indeed declined significantly over the last decade (LVFO, 2008). SIMONIT and PERRINGS (2005) asserted that landings of all [our italics] fish had declined since 1994 and, while recognising the contribution of overfishing, suggested that eutrophication was an important factor.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, during the Nile perch boom, from 1987 to 1990, Nile perch densities were homogeneous across the regions of Mwanza and Speke Gulf (Goudswaard et al, 2008). More recent stock assessments through bottom trawling and catch assessments of Nile perch in the Tanzanian part of the lake from 1997 to 2002 showed that Nile perch aggregated on a very local and temporal scale in shallow and deep waters and at different depths of the water column (Mkumbo, 2002;Mkumbo et al, 2007). However, on a large spatial scale, there was no consistent pattern in Nile perch densities between the east, west and south side of the Tanzanian part of the lake or between different depths up to 50 m (Mkumbo, 2002;Mkumbo et al, 2007).…”
Section: Regional Scalementioning
confidence: 99%
“…Since the start of the fisheries concerns have been voiced that Nile perch stocks are declining and may collapse if fishing pressure will continue to increase (Mkumbo, 2002;Balirwa et al, 2003;Getabu et al, 2003;Ogutu-Ohwayo, 2004;Matsuishi et al, 2006;Mkumbo et al, 2007). However, stock assessments based on Nile perch catches and population size structure showed no signs of overfishing or long-term decline of the Nile perch stock, although, since the 1990s the stock shows short-term decadal fluctuations (Kolding et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations